Vitamin D and calcium status in children with thalassemia beta major: A cross sectional study in Banda Aceh - RR. Rima Aulia Fiska; Eka Destianti Edward; Eka Yunita Amna; Heru Noviat Herdata; Nora Sovira; Jufitriani Ismy (AcTion: Aceh Nutrition Journal, 2025)
Frequent blood transfusions in children with beta-thalassemia major result in iron overload, leading to hemosiderosis in various body tissues, and impair the function of these organs, disrupting vitamin D metabolism, which contributes to osteoporosis and other morbidities, which are believed to be associated with hypocalcemia, which significantly affects growth. This study aimed to investigate the relationship between vitamin D and calcium status in children with β-thalassemia major at dr. Zainoel Abidin Public Hospital in Banda Aceh, Indonesia. Methods: An analytical observational study employed a cross-sectional design involving 40 children aged 2–18 years with a beta-thalassemia major attending the Children's Thalassemia Clinic at dr. Zainoel Abidin Public Hospital in Banda Aceh, Indonesia. from July to November, 2024. Categorical data were analyzed using the Spearman test, with a p-value of <0,05. Results, of the 40 subjects, 55% subjects were male, in 45% of subjects, there was Vitamin D deficiency, 25% was vitamin D insufficiency, hypocalcemia in 77,5% subjects. Among subjects with vitamin D deficiency, 94,4% also had hypocalcemia (r = 0,037, p = 0,017). In conclusion, there was a significant association between vitamin D and calcium status in children with beta-thalassemia major.